Balance hídrico de dos cuencas de encinar de la Serra de Prades (Tarragona) - Lledó M.J.; Piñol J. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Here is the hydrological record (rainfall and streamflow) of two impervious watersheds paired and covered by a dense Quercus ilex forest. They are located in the Serra de Prades (Tarragona, Spain) where the climate is typically Mediterranean. The recording period started in October 1981 for Cl and in July 1986 for C2. The 79-month hydrological record of Wl allows us to make the following observations: 1) most of the precipitation is evapotranspirated (92 per cent); 2) the volumes of annual streamflow and evapotranspiration show an important interannual variability. The 22-month simultaneous hydrological record of W1 and W2 show us that: 1) C2 drains out almost twice as much water as Cl; nevertheless, because the absolute amounts of streamflow are so small, the actual evapotranspiration remains quite similar in both watersheds; 2) differences between Cl and C2 streamflows are mainly due to quickflow rather than to baseflow, and reflect the particular morphology of each watershed.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)